2006
DOI: 10.1007/bf02784707
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of genetic diversity for ecosystem functioning: Estuarine macrophytes as models

Abstract: Recent experiments in macrophyte dominated communities on the relationship between biological diversity and ecosystem functioning suggest that effects and mechanisms of genetic-genotypic and species diversity are analogous. As previously shown for species diversity, genotypic diversity enhances ecosystem productivity and recovery from disturbance. These findings generalize ecological theory, and provide an empirical basis for explicitly considering the maintenance of genetic or genotypic diversity for conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 54 publications
1
62
0
Order By: Relevance
“…Although the species richness and biotic diversity of macrophytes within the adjacent salt marsh and eelgrass communities in the South Slough are relatively low, the genotypic and genetic diversity of these systems is unknown. Recent investigations of genetic diversity within beds of Zostera marina (OLSEN et al, 2004;REUSCH and HUGHES, 2006) indicate that the diversity of nuclear recombinant DNA and several microsatellite loci can be substantial within single-species beds tested in temperate Atlantic and Pacific estuaries. In addition, HUGHES and STACHOWICZ (2004) found that Z. marina beds with high genetic diversity were correlated with higher plant densities in winter months and with enhanced use of pore water nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the species richness and biotic diversity of macrophytes within the adjacent salt marsh and eelgrass communities in the South Slough are relatively low, the genotypic and genetic diversity of these systems is unknown. Recent investigations of genetic diversity within beds of Zostera marina (OLSEN et al, 2004;REUSCH and HUGHES, 2006) indicate that the diversity of nuclear recombinant DNA and several microsatellite loci can be substantial within single-species beds tested in temperate Atlantic and Pacific estuaries. In addition, HUGHES and STACHOWICZ (2004) found that Z. marina beds with high genetic diversity were correlated with higher plant densities in winter months and with enhanced use of pore water nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of factors that contribute to local differences in the community composition of estuarine salt marshes and eelgrass beds is intriguing because low taxonomic richness within these communities contradicts the view that species diversity is positively correlated with enhanced ecosystem functions (LOREAU et al, 2001;REUSCH and HUGHES, 2006). The rationale for our concurrent approach of characterizing eelgrass beds and salt marsh communities is that the combination of time-series information from several different types of ecological components (ambient water column parameters, dissolved nutrients, salt marshes, eelgrass beds, and macroalgae) provides a more robust indicator of the condition of plant communities in the South Slough estuary than the limited information derived from any single component.…”
Section: Introductionmentioning
confidence: 99%
“…As seed banks provide a genetic reservoir for changing environmental conditions, subsequent recruitment can strongly influence population structure and genotypic diversity, especially for clonal plants (Eriksson 1989, Morris et al 2002, Koch et al 2003, Barrett et al 2005, Reusch et al 2005, Reusch 2006, Reusch & Hughes 2006, After the near total loss of subtidal eelgrass Zostera marina meadows to a wasting disease in the early 1930s, dwarf eelgrass Z. noltii has emerged as the primary seagrass species inhabiting the Wadden Sea, particularly in the northern regions (Reise & Kohlus 2008). Dwarf eelgrass is usually confined to the upper intertidal zone of sheltered sandy and/or muddy European coastlines, but sometimes it is found in the shallow subtidal zone (den Hartog 1970).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that genetic diversity is only important in ecosystems that rely on or are dominated by one or a few key or habitat providing species, such as Zostera marina ecosystems (Hughes et al, 2008). However, all living organisms are hierarchically organized: genes make up genotypes, genotypes define populations and populations collectively constitute a species (Reusch & Hughes, 2006). If there is variation and heritability, as well as selection in ecologically important traits such as, e.g., growth rate or resistance to parasites, diversity at any level can have important ecological effects (Hughes et al, 2008).…”
Section: Integrating Species and Genetic Diversity In One Experiment:mentioning
confidence: 99%
“…It is therefore fundamental to start to include changes in genetic (population) and species diversity in studies assessing the consequences of biodiversity decline. Today, Zostera marina vegetations probably provide the best systems to investigate species and genetic diversity in concert (Reusch & Hughes, 2006). To our knowledge, it is also the only system where genotypic (seagrass) and species (grazer) diversity have been manipulated simultaneously (Hughes et al, 2010).…”
Section: Integrating Species and Genetic Diversity In One Experiment:mentioning
confidence: 99%